Mediating Academic Writing in The Age of Generative AI: EFL Lecturers’ and Students’ Perspectives on Proposal Writing Accuracy - Dayat, Dayat; Kurniawati, Tri (J-SHMIC : Journal of English for Academic, 2026)
This study explores lecturer mediation in undergraduate academic writing within an English as a Foreign Language (EFL) higher education context. Employing a qualitative case study design, data were collected from lecturers' written feedback on students’ research proposals, semi-structured interviews with lecturers and students, and a focus group discussion (FGD). The study addresses four research questions examining the forms of lecturer mediation, its contribution to students’ academic writing quality, and how such mediation is perceived and positioned by both students and lecturers. The findings reveal that lecturer mediation primarily focuses on higher-order academic concerns, including research focus, argumentation, and methodological coherence, rather than surface-level language correction. Lecturer feedback plays a central role in improving students’ academic writing accuracy and guiding their academic reasoning. Both students and lecturers consistently position lecturer mediation as the most authoritative form of academic writing support, particularly for validating research direction and methodological soundness. Importantly, the study also demonstrates that lecturer mediation can be pedagogically integrated with the use of generative artificial intelligence (AI) in academic writing instruction. While students tend to use generative AI tools for linguistic support, such as grammar checking and paraphrasing, lecturer mediation remains essential for epistemic guidance, critical evaluation, and academic judgment. This integration highlights the continued relevance of lecturer mediation in ensuring that academic writing remains a meaningful learning process in EFL contexts. The study contributes to current discussions on academic writing pedagogy by proposing a mediated approach to the responsible use of generative AI in higher education.